Pengaruh Due Profesional Care, Etika Audit, Kompleksitas, Dan Fee Audit Terhadap Kualitas Audit (Studi Pada Kantor Akuntan Publik (KAP) Kota Bandar Lampung Dan Palembang) - Eka Sariningsih; elia puspita sari (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2012)
Abstract, This research is important to know, analyze, and get empirical evidence about the influenceof due professional care, audit ethics, complexity, and audit fee on audit quality at public accountingfirm (KAP) Bandar Lampung City and Palembang. The unit of analysis in this study are all publicaccounting firms Bandar Lampung and Palembang. The sampling method is saturated, with a total of57 respondents with an 84% return rate. Data analysis technique used is Partial Least Square (PLS)model. PLS is a structural equation model (SEM).The result of the analysis shows that professional care has a significant effect on audit quality, auditethics has significant effect on audit quality, the complexity does not affect the quality of audit, auditfee has a significant effect on audit quality.